2002
DOI: 10.1016/s1386-9477(01)00426-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of correlated disorder potentials on the levitation of current carrying states in the quantum Hall effect

Abstract: The disorder driven quantum Hall to insulator transition is investigated for a two-dimensional lattice system. We consider a Gaussian correlated random potential, study the behaviour of the current carrying states and trace their energetical position when the disorder strength is increased. Our results qualitatively resemble those obtained previously for exponentially correlated disorder potentials. We find both the downward movement of the anti-Chern states as well as the floating up of the Chern states acros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Using spatially correlated random disorder potentials instead, it could be shown that the effect of the anti-Chern states is reduced so that the expected levitation scenario and the floating of current carrying states across the Landau gap is seen also in the lattice model. 29,30 These results also imply that, contrary to other claims, 23,26 the direct transitions to the Hall insulator occurring within the lattice model with uncorrelated disorder potentials can of course not be held responsible for the direct transitions seemingly observed in experiments. 11 Here, finite size effects and limited resolution due to finite temperatures are the most probable causes 32 that account for the reported behavior.…”
Section: Introductioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Using spatially correlated random disorder potentials instead, it could be shown that the effect of the anti-Chern states is reduced so that the expected levitation scenario and the floating of current carrying states across the Landau gap is seen also in the lattice model. 29,30 These results also imply that, contrary to other claims, 23,26 the direct transitions to the Hall insulator occurring within the lattice model with uncorrelated disorder potentials can of course not be held responsible for the direct transitions seemingly observed in experiments. 11 Here, finite size effects and limited resolution due to finite temperatures are the most probable causes 32 that account for the reported behavior.…”
Section: Introductioncontrasting
confidence: 54%
“…The results of the numerical work for a disordered twodimensional lattice model can be summarized as follows: There is a genuine floating of the critical states to higher energies. 21,24,25,[28][29][30][31] This floating is, however, not easy to observe in systems with uncorrelated random disorder potentials due to a peculiar annihilation mechanism inherent in the lattice model. In this model the Chern states, which correspond to the critical electronic states in each Landau band that are responsible for the integer quantized Hall conductivity, get neutralized by the so called anti-Chern states originating from the center of the tight-binding band.…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, long-range spatial correlation can result in the delocalization for the 1D Anderson model. [17] It was shown that even the short-range correlated disorder models, such as the random-dimer model, [18,19] can exhibit an absence of localization. In this study, we show that the localization properties of the disordered systems can be well researched by using of the measure of concurrence.…”
mentioning
confidence: 99%
“…We normalize the power-law correlated site energies to the range [−W, W ] in the calculation. The Gaussian correlated disorder site energies are generated as follows: [18] (A) generating the uniform distributed random energies ε i at the interval of [−W, W ]; (B) the Gaussian correlated disordered random site energies are obtain by the following aver-…”
mentioning
confidence: 99%